Prioridades estratégicas, ferramentas de controle gerencial e desempenho : um estudo empírico em empresas industriais paranaenses - Panosso, Alceu (2015)
This study aimed to investigate the influence of the strategic priorities in the adoption of management control tools and performance of Paraná industrial companies, and the influence of the adoption of management control tools in the performance of Paraná industrial companies. On the characterization of the study questioning the following research questions were established: What is the influence of the strategic priorities in the adoption of management control tools and performance of Paraná industrial companies? What is the influence of the adoption of management controls tools in the performance of the state's industrial companies? As support data analysis was carried out a literature review dealing on the following topics: Contingency Theory; Organizational strategy; Systems management controls involving management control in organizations, management and performance evaluation of management controls and tools. Design Methodology defined by the classification of research on the technical procedures and objectives; the object of study population comprised 1809 companies registered in FIEP (Federation of Paraná State Industry), where 1365 are medium sized companies with 100-499 large employees and 444 with 500 or more employees, with a valid sample of 149 companies. The data collection instrument was given by questionnaire. For data analysis we used logistic regression, analysis of variance: ANOVA test and Chi- square. For the analysis of the results it was possible to realize the importance of the strategic priorities for the management of companies, found that most managers know the tools of management controls, with a low percentage of use and that many deem important, but do not use. It was also found through research that the strategic priorities of differentiation showed that there was influence on the use of only three management control tools, budgeting, cost / volume / profit and the Balanced Scorecard; and cost leadership in both tools, the ABM management and analysis of economic measures of performance, but both had big influences on business performance. There was also that only the use of one of the tools in the study had an influence on business performance target of research, and therefore the budget.